PERCEPTION AND ACCEPTANCE OF STAKEHOLDERS IN AGRICULTURAL INTERVENTION PROGRAM FOR IMPROVEMENT OF FOOD AND NUTRITION SECURITY IN EAST JAVA, INDONESIA - Mariyono, Joko; Kuntariningsih, Apri (Sosiohumaniora, 2024)
A program intervention has been launched to achieve food and nutrition security in Indonesia. However, the process and implementation are supposed to be smoother than anticipated. This research analyzes the involvement and roles of stakeholders and organizations in implementing the program as the factors affecting the process’s smoothness. This research espoused an actor and institution-centered communication approach to dissect the stakeholders directly and laterally involved in executing the program. The East Java region was selected as the study sample. A qualitative ethnographic-phenomenological approach was adopted for this study. The crucial snatchers include government officers, extension workers, original leaders, and growers. Data were compiled using direct interviews and focus group discussions. This study applied triangulations among government organizations, stakeholders, and end-druggies to corroborate the data and information. Results of the analysis show that the dispatches of actors and institutions played dominant roles in the program’s execution. In the early application stage, the dominant role of actor and institution communication was explosively needed in a new program intervention to smooth implementation. In the provincial position, government officers played significant communication roles. The main actors in the program included women leaders of ménage substance education and farmer leaders at the grassroots position. Agrarian extension officers dominantly communicated between parochial and grassroots situations. The roles and involvements of the stakeholders varied across stages of program implementation. Institutions should reduce the dominant roles of their staff members in the late stages, engage local champions to replace the staff members, and substantially lessen reliance on formal institutions.